Efforts to Prevent Turnover Intention OnTajur Bag Without SKI Brand in Bogor City, West Java Province - ISMARTAYA ,; INDAH PERMATA ,; AGUSTINA SOLEHAH, (KRIDA CENDEKIA, 2023)
The purpose of the research is to find out what are the causes of turnover intention and what efforts have been made by the company to prevent this turnover intention. This research was conducted by observation and interview directly with operational managers and workers who work in Tas Tajur without brand SKI, as well as conducting library studies. So it resulted that in Tas Tajur Tanpa Merk was found some indications of turnover intention that has reached labour turnover, one of which is the increasing level of attendance of labor. This research is expected to be useful for companies in order to reduce turnover intention and prevent the occurrence of labour turnover.